(untitled) (Ciencia y Sociedad, 2008)
In a descriptive, multicentric, epidemiologist study , performed in a sample of 150 patients, men and women, older than 20 years, in nine hospitals of the country, the prevalence of undernourishment was of 53 % according to the Subjective Global Valuation and 67 % according to the Specialized Nutrition Valuation, and 15 % had severe undernourishment. The daily consumption of the different foods was the following: meat and eggs (23 %), lacteal foods (34 %), fruits and juices (34 %), vegetables (14 %). 35 % of the undernourished consume meat and eggs less than three times per week, whereas among the nourished , the number was smaller (16 %). 12 % of the undernourished and 4 % of the nourished had fasted for more than 5 days while they were hospitalized. According to the nourishing reminder of 24 hours of the previous day, 81 % of the patients ingested 30 kcal/kg/day less than the well-nourished, and 55 % received less than 20 kcal/kg/day. 53 % had not ingested proteins in the last 24 hours.